Respuesta :
Answer:
B. [tex]\frac{1}{28^2}[/tex]
C. [tex]\frac{7^{-2}}{4^2}[/tex]
Step-by-step explanation:
The given expression is [tex]4^{-2}*7^{-2}[/tex]
We can rewrite in various forms using the rules: [tex](a^m)^n=a^{mn}[/tex] and [tex]a^{-m}=\frac{1}{a^m}[/tex]
For instance
[tex]4^{-2}*7^{-2}=\frac{1}{4^2}*\frac{1}{7^2}=\frac{1}{(4*7)^2}=\frac{1}{28^2}[/tex]...Option B
OR
[tex]4^{-2}*7^{-2}=\frac{7^{-2}}{4^2}[/tex]....Option C
Therefore options B and C are correct
Answer:
B and C
Step-by-step explanation:
4^-2 can also be written as 1/4^2 and so can 7^-2